2016
DOI: 10.1038/npp.2016.114
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Medial and Lateral Frontal-Striatal Circuits in Cocaine Users and Controls: An Interleaved TMS/BOLD Functional Connectivity Study

Abstract: The integrity of frontal-striatal circuits is an area of great interest in substance dependence literature, particularly as the field begins to develop neural circuit-specific brain stimulation treatments for these individuals. Prior research indicates that frontal-striatal connectivity is disrupted in chronic cocaine users in a baseline (resting) state. It is unclear, however, if this is also true when these circuits are mobilized by an external source. In this study, we measured the functional and structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 57 publications
3
54
0
Order By: Relevance
“…They also demonstrated that activity in the DLPFC was inversely related to activity in the MPFC. However, our group has previously shown that the reciprocal relationship found between executive control and default mode networks in healthy controls is not present in cocaine users (Hanlon et al, 2016b). That is, stimulating the DLPFC did not have a significant attenuating effect on MPFC activity in cocaine users.…”
Section: Discussionmentioning
confidence: 95%
“…They also demonstrated that activity in the DLPFC was inversely related to activity in the MPFC. However, our group has previously shown that the reciprocal relationship found between executive control and default mode networks in healthy controls is not present in cocaine users (Hanlon et al, 2016b). That is, stimulating the DLPFC did not have a significant attenuating effect on MPFC activity in cocaine users.…”
Section: Discussionmentioning
confidence: 95%
“…fMRI-rTMS studies in healthy controls have directly demonstrated that rTMS pulses to the frontopolar cortex caused BOLD activations in both the frontal pole and in the ventral striatum; rTMS pulses to the dlPFC, in contrast, caused BOLD activations in both the dlPFC and the dorsal caudate nucleus (Hanlon et al, 2013, 2016). A session of inhibitory, continuous theta-burst stimulation to the frontopolar cortex reduced the BOLD response to individual pulses at the same target, with the effect seen prominently in ventral striatum (Hanlon et al, 2015).…”
Section: Targeting the Sn-cstc With Therapeutic Brain Stimulationmentioning
confidence: 99%
“…Aside from the well-established example of SUD, pathology of this loop may be important in OCD, MDD (particularly for the symptom of anhedonia), schizophrenia, and other psychiatric disorders (as noted throughout the previous three sections of this review). In addition, interactions (such as mutual inhibition) between the activity of the dorsal striatal-SN loop and the ventral striatal reward loop may be important for understanding psychiatric pathology and its heterogeneity; such interactions between dorsal and ventral CSTC loops are an increasingly prevalent theme of study in recent work combining neuroimaging and neurostimulation in psychiatric illness (for example, Liston et al, 2014; Hanlon et al, 2016). …”
Section: Unresolved Questions and Future Directions For Studymentioning
confidence: 99%
“…Having demonstrated that it was possible to differentiate these circuits in controls, the next step was to evaluate the integrity of these circuits in cocaine users [36]. Eighteen cocaine-dependent individuals with a history of failed quit attempts and 18 age-matched controls were recruited from the community.…”
Section: Study 2: Which Circuit Is More Disrupted In Cocaine Users?mentioning
confidence: 99%